Evaluate the role of the judiciary in interpreting strike laws and determining the legality of industrial action - Ismail, Fadillah (Journal of Islamic, Social, Economics and Development, 2025)
The Malaysian judiciary plays a crucial role in shaping employee relations by interpreting and enforcing strike laws. This paper examines how the judiciary balances employees' rights to protest with the broader public interest, particularly in essential services. This study contributes significantly to understanding how the role of the judiciary in Malaysia can be strengthened through improvements to the alternative industrial dispute resolution (ADR) system, as well as proposing reforms to the Industrial Relations Act 1967 to better align it with the principles of workers' freedom of expression and international labour standards. The judiciary's role in determining the legality of industrial action, including wildcat strikes, and its efforts to promote alternative dispute resolution (ADR) are explored. Challenges such as the time-consuming nature of legal processes and restrictions on essential services can hinder employees' ability to exercise their right to strike effectively. This study finds that judicial interpretations of strike laws in Malaysia tend to prioritise economic stability and the public interest, particularly in essential services sectors, over comprehensive protection of workers' rights to take lawful industrial action. To enhance industrial relations, the paper recommends streamlining judicial processes, promoting ADR, updating strike laws, strengthening trade unions, and fostering public awareness. By adopting these recommendations, Malaysia can create a more harmonious and equitable workplace for all.